The Effect of Rhythmic Tactile Stimuli Under the Voluntary Movement on Audio-Tactile Temporal Order Judgement - Tanaka, Taeko; Ogata, Taiki; Miyake, Yoshihiro (Frontiers in Psychology, 2021)
The simultaneous perception of multimodal sensory information is important for effective reactions to the external environment. In relation to the effect on time perception, voluntary movement and rhythmic stimuli have already been identified in previous studies to be associated with improved accuracy of temporal order judgments (TOJs). Here, we examined whether the combination of voluntary movement and rhythmic stimuli improves the values of just noticeable difference (JND) in audio-tactile TOJs. Four different experimental conditions were studied, involving two types of movements (voluntary movement, no movement) and two types of stimulus presentation (rhythmic, one-time only). The stimuli were provided in a rhythmic or one-time only manner by hitting the belly of the participants’ right index finger using a tactile device. In the voluntary movement condition (VM), participants moved their right index finger voluntarily and naturally, and in the no-movement condition (NM), their right index finger attached to the tactile device was moved by the programming. Furthermore, in the rhythmic stimuli conditions (RT), tactile stimuli were presented rhythmically to the right index finger 5 times consecutively. Participants made an order judgment for the fifth tactile stimuli and the first and only auditory stimuli. In our TOJ task, auditory-tactile stimulus pairs were presented to participants with varying stimulus-onset asynchronies (SOAs; intervals between the within-pair onsets of the auditory and tactile stimuli). For the two stimuli presented at a time that were shifted by the SOA, the participants were asked to judge which one was presented first, and they were given a two-choice answer. Our results showed a significant interaction between the two types of movements (VM, NM) and the two types of stimulus presentation (RT, 1T). The JND of the RT performed better than 1T in the NM condition, while the JND of 1T was better in the VM condition than RT. These results indicate that the JND value was not reduced by the combination of VM and RT conditions.